2003
DOI: 10.1046/j.1468-1293.2003.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV lipodystrophy: prevalence, severity and correlates of risk in Australia

Abstract: ObjectiveTo establish the prevalence, severity and factors associated with the HIV lipodystrophy syndrome. MethodsCross-sectional study of lipodystrophy conducted in high HIV caseload primary care sites and HIV outpatient clinics. A subset of patients was examined using dual energy X-ray absorptiometry (DEXA) and single cut abdominal computerized tomography (CT) at the L4 vertebral level to quantify regional and total body fat. Factors associated with lipodystrophy, lipoatrophy and lipohypertrophy were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
141
7
12

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(173 citation statements)
references
References 17 publications
13
141
7
12
Order By: Relevance
“…The strong, inverse correlations of baseline BMI and body composition parameters such as limb fat, limb fat percentage and VAT with subsequent limb fat loss suggest that individuals with greater pretreatment limb fat are more likely to experience peripheral fat loss, perhaps because such patients have more fat to lose. This finding conflicts somewhat with earlier cross-sectional studies that showed that lipoatrophy was more common in patients who were emaciated [2].…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…The strong, inverse correlations of baseline BMI and body composition parameters such as limb fat, limb fat percentage and VAT with subsequent limb fat loss suggest that individuals with greater pretreatment limb fat are more likely to experience peripheral fat loss, perhaps because such patients have more fat to lose. This finding conflicts somewhat with earlier cross-sectional studies that showed that lipoatrophy was more common in patients who were emaciated [2].…”
Section: Discussioncontrasting
confidence: 95%
“…The strong, inverse correlations of baseline BMI and body composition parameters such as limb fat, limb fat percentage and VAT with subsequent limb fat loss suggest that individuals with greater pretreatment limb fat are more likely to experience peripheral fat loss, perhaps because such patients have more fat to lose. This finding conflicts somewhat with earlier cross-sectional studies that showed that lipoatrophy was more common in patients who were emaciated [2].The association between plasma leptin levels and the development of lipoatrophy was investigated in lipoatrophic HIV-infected males in a nested case-control study (10 cases and 87 controls) from the Swiss HIV Cohort Study. At 2 years, there was no difference in leptin levels between patients who developed clinically assessed lipoatrophy and controls, with age the only predictor of lipoatrophy [19].…”
contrasting
confidence: 59%
See 1 more Smart Citation
“…The prevalence of lipodystrophy in any of the three forms of manifestation (lipoatrophy, lipodystrophy or mixed) is not well established in the literature. The fact that there is no consensus on the diagnostic method and the differences in the studied populations may account for variation between studies [19][20][21][22] . In a review by Tien and Grunfeld 23 , several studies on lipodystrophy were analyzed, which reported that the rates of lipodystrophy range from 30% to 62%.…”
Section: Discussionmentioning
confidence: 99%
“…61,62 Recent studies of adipose tissue biopsies from 'naive' patients have revealed the first signs of mtDNA depletion 63 as well as some impairment of the expression of genes encoding mitochondrial proteins, adipocyte differentiation controllers such as PPARg and proteins specifically related to adipocyte metabolism including adipokines such as adiponectin. 17 This is associated also with increased TNFa gene expression in these patients.…”
Section: Lipomatosis In Hals Reveals a Potential For Brown Adipocyte mentioning
confidence: 99%